PENURUNAN KADAR LOGAM KADMIUM PADA UDANG (Peanaeus merguiensis) DENGAN PERENDAMAN CUKA NIRA ENAU (Arenga pinnata) - Manu, Rolin M. P.; Tambaru, David; da Cunha, Theo (Universitas Nusa Cendana, 2018)
A research on the decrease of cadmium (Cd) content in shrimps by soaking them in palm (Arenga Pinnata) vinegar has been done. This study aimed to determine the removal percentage (%) of cadmium from shrimp after immersed in palm (Arenga Pinnata) vinegar and to determine the concentration and immersion time optimum in reducing the cadmium metal content in shrimps. The research was conducted in several steps namely sample preparation, determination of optimum concentration of vinegar, simulation of shrimp pollution, sample soaking in palm (Arenga Pinnata) vinegar and determination of cadmium content in samples. A two-way ANOVA test (α = 0,05) showed that the variation of palm (Arenga Pinnata) vinegar concentration has significant effect on reducing Cd content, while contact times have no significant effect on the reduction of Cd content in shrimps. It was found that the optimum concentration of palm (Arenga Pinnata) vinegar was 2% and optimum immersion time was 30 minutes. The removal percentage (%) of cadmium content from shrimps using palm vinegar reached 98.84%.